LEARNING VOCABULARY BASED ON EDUCATION ENVIRONMENT - Sabil, Marhaeni (JKIP (Jurnal Keguruan dan Ilmu Pendidikan), 2015)
The writer focused on problem statement into one question as follow: Can education environment develop students’ vocabulary of STIE Amkop Makassar?. This study aims to find out that education environment can develop students’ vocabulary of STIE Amkop Makassar. The significant of this study is expected to give useful information on English teaching and learning process, especially in learning English vocabulary based on education  environment. In this case the researcher used experimental as a research method, and She used random sampling technique in chooosing sample. Vocabulary test as research instrument, it consist of 20 items, then  pretest and posttest was used to collected data, statistic analysis as a techniques of data analysis. Based on the result of the data analysis and the discussion of the result in the previous chapter, the writer would like to put forward conclusion that the school environment is a good medium in teaching-learning process specially to develop students’ vocabulary of STIE Amkop Makassar.